Small Displacement Detection of Biological Signals Using the Cyclic Frequency Method - Dan Zhang; Masahiko Kurata; Takayuki Inaba (International Journal of Antennas and Propagation)
A new signal processing method called the Cyclic Frequency method is proposed for small displacement detection of vital signals such as heart rate and respiration using the CW radar method. We have presented experimental results of small displacement detection to confirm the validity of the method. The displacement amplitude 2.5 mm can be detected with a propagation frequency of 24.15 GHz. We may increase the propagation frequency for smaller displacement amplitude or target velocity.